Data from: When the "selfish herd" becomes the "frozen herd": spatial dynamics and population persistence in a colonial seabird ... - McDowall, Philip; Lynch, Heather (Dryad, 2019)
Aggregations are common in ecological systems at a range of scales and may be driven by exogenous constraints such as environmental heterogeneity and resource availability or by 'self-organizing' interactions among individuals. One mechanism leading to self-organized animal aggregations is captured by Hamilton's ‘selfish herd’ hypothesis, which suggests that aggregations may be driven by an individual's effort to minimize their risk of predation by surrounding themselves with conspecifics. We demonstrate that aggregations observed in Adélie penguin (Pygoscelis adeliae) colonies are a convolution of both self-organized dynamics and external forcing arising from landscape terrain. In fluid, highly mobile aggregations, individuals are constantly moving in response to changing environmental conditions, the locations of predators, or the movements of conspecifics. However, when the ability to rearrange is limited and spatial reconfiguration occurs on slower time scales than changes in population size, systems may ... : McDowall and Lynch Supplementary DataShapefile containing all 1,893,597 hexagonal cells, along with information on each cell's elevation, slope, cost-weighted distance to shore, flow accumulation, occupancy status (occupied vs unoccupied), and number of first-order neighbors. See Appendix S1 for further details. ...